'Thou shalt not kill' : missionaries in Asia during the World Wars, 1914-1946. - United Society for the Propagation of the Gospel (East Ardsley, Wakefield, United Kingdom : Microform Academic Publishers, 2015)
This collection contains first hand accounts by missionaries attached to The Propagation of the Gospel (SPG) both during peacetime and the turmoil of the World Wars. The SPG was a Church of England missionary organisation active across the world in the spreading of Christianity during the colonial period. The subject matter largely pertains to SPG missionaries' experience of Japanese expansionism during the Second World War. Missionaries had a range of penal punishments brought against them, including internment, house arrest, and assignment to work camps. Others attached to the SPG fled their assigned countries by any means necessary. As such, the collection offers both personal experiences of the Second World War, as well as how the SPG as an organisation coped with its intrusion. Missionaries' accounts from Japan, Burma (modern day Myanmar), China, Singapore, and Malaysia are the main focus of the collection.
Date range: 1914-1946.
Keywords: Missionaries -- Great Britian -- Biography; World War, 1939-1945 -- Asia -- Personal narratives; World War, 1914-1918 -- Asia -- Personal narratives; Society for the Propagation of the Gospel in Foreign Parts (Great Britain) -- Biography